Characteristics and mechanism of styrene cationic polymerization in 1-butyl-3-methylimidazolium hexafluorophosphate ionic liquid. Issue 107 (4th November 2016) - Han, Lu; Wu, Yi-bo; Dan, Yang; Wang, Hao; Zhang, Xiao-qian; Wei, Xu-ling; Guo, Wen-li; Li, Shu-xin
Abstract : There has recently been a wide range of trends in the use of ionic liquids (ILs) as reaction solvent for various polymerization processes. Abstract : There has recently been a wide range of trends in the use of ionic liquids (ILs) as reaction solvent for various polymerization processes. A series of cationic polymerizations of styrene in 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim][PF6 ]) had been achieved using a variety of coinitiators combined with a, a -dimethylbenzyl chloride (CumCl) as a initiator at −15 °C. Experiments were carried out to observe the influence of solvent polarity and viscosity on polymerization rate. Compared with those in organic solvents, the cationic polymerization of styrene in [Bmim][PF6 ] proceeded in a milder exothermic manner. The end-group structures of the polystyrenes were identified by 1 H NMR spectroscopy and MALDI-TOF-MS. The corresponding elementary reactions and mechanism of styrene cationic polymerization in [Bmim][PF6 ] were also discussed.